2021
DOI: 10.3390/v13030371
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes towards Anti-SARS-CoV2 Vaccination among Healthcare Workers: Results from a National Survey in Italy

Abstract: Coronavirus disease 2019 (COVID-19) has afflicted tens of millions of people, fostering and unprecedent effort in vaccine development and distribution. Healthcare workers (HCW) play a key role in vaccine promotion and patient guidance, and it is likely that hesitancy among this population will have a major impact on the adoption of a successful immunization policy. To investigate HCW attitudes towards anti-severe acute respiratory syndrome coronavirus 2 (SARS-CoV2) vaccination, we developed an anonymous online… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

20
150
13
12

Year Published

2021
2021
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 153 publications
(208 citation statements)
references
References 25 publications
20
150
13
12
Order By: Relevance
“…The primary source of COVID-19 news was not associated with the intent to vaccinate nor with the knowledge score. This is in contrast with some other studies, where people receiving COVID-19 information from social media had higher levels of vaccine hesitancy [ 25 ]. Our participants were neutral to the geographic origin of vaccine development, as they did not favor a vaccine developed in America or Europe over any other country.…”
Section: Discussioncontrasting
confidence: 96%
“…The primary source of COVID-19 news was not associated with the intent to vaccinate nor with the knowledge score. This is in contrast with some other studies, where people receiving COVID-19 information from social media had higher levels of vaccine hesitancy [ 25 ]. Our participants were neutral to the geographic origin of vaccine development, as they did not favor a vaccine developed in America or Europe over any other country.…”
Section: Discussioncontrasting
confidence: 96%
“…Another reason could be related to the nature of the study design, this study could have been more biased towards the young, as the elderly are less likely to engage with online-based surveys. Moreover, there are contrasting reports of gender effects in the literature, wherein some males were more likely to accept the vaccine [25,35], compared to others reporting higher acceptance among females [21,32]. In our study, Jordanian males were more likely to take the vaccine, in agreement with studies reported elsewhere [25].…”
Section: Discussionsupporting
confidence: 86%
“…After the 10 March 2021, 59% of respondents to the poll were already vaccinated against COVID-19, versus 46% in the national surveillance of French healthcare workers [ 15 ]. Since mid-2020, 15 studies investigated the willingness, and 3 reported the scaling-up of COVID-19 vaccination among healthcare professionals [ 14 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 ]. Taken together, we can estimate the overall willingness to get vaccinated at 65% (95CI 56% to 73%) among healthcare workers, with a prediction interval ranging from 18% to 94%, and varying by region of the globe ( Supplementary Figure S3 ).…”
Section: Discussionmentioning
confidence: 99%